Application of Flow Cytometry to Determine Cell DNA Content in the Genetic Breeding of Fish - Xinyan Zhu; Yang Chen; Xiaodie Zhang; Jiaxu Qiang; Lingtao Nie; Xinyue Luo; Binchao Liang; Kuo Chen; Fuzhong Yang; Rurong Zhao; Chun Zhang (Fishes)
In the field of fish genetic breeding, accurately determining the DNA content and ploidy of fish is of great significance. This article introduces the use of flow cytometry (FCM) to measure the DNA content and conduct ploidy analysis by sampling different tissues of freshwater fish species. It describes the FCM detection methods and their effectiveness for different individual tissues. These tissues include embryos and fry, as well as the blood, caudal fins, and sperm of adult live fish, and also specific tissues such as testes, ovaries, gills, spleens, and livers under anatomical conditions. Moreover, the application of ploidy detection to different tissues or individuals in different stages in the practice of fish genetic breeding is analyzed. This research covers samples from different growth stages and a variety of tissue types. The results show that this method exhibits high stability and reliability in the detection of different tissue samples, providing solid data support for subsequent research. It holds significant application value in fish genetic breeding.